Do Staple Food Consumption Patterns Affect Household Food Waste in Rural China? - Nanyan Hu; Jiachen Guan; Yonghao Hu; Laping Wu (Foods)
This study utilizes a national database derived from large-scale surveys to examine the impact of staple food consumption patterns on household food waste in rural China. Using the Tobit model, the findings show that staple food consumption significantly influences food waste. Specifically, southern households, where rice is the staple food, waste 44% more food than their northern counterparts, where wheat is the staple. To address potential self-selection bias, the study employs the propensity score matching (PSM) model to validate the robustness of these results. Further heterogeneity analysis shows that the effect of staple food consumption on food waste is more pronounced in larger rural households with children. These results underscore the importance of dietary culture in explaining regional disparities in food waste across China.